THE PRODUCTION AND PURIFICATION OF CANDIDATE RECOMBINANT CHIMERIC IgA-IgG AGAINST DENGUE VIRUS IN CHO-K1 CELLS - , DWI PURNO WIDEKDO, Prof. dr. Sofia Mubarika, M.Med.Sc. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
-